Untersuchungen zum ländlichen Raum der Wikingerzeit.: Ein neuer Fundplatz bei Bohnert (Gem. Kosel) - Palmowski, Valerie; Schade, Tobias; Mennenga, Moritz (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
Metal detector surveys by a member of the ›Detektorgruppe Schleswig-Holstein‹ have recently revealed a new archaeological site (LA 89) near Bohnert, in the municipality of Kosel, district of Rendsburg- Eckernförde. Due to the detector finds, which among other objects yielded an equal-armed brooch, dirhams, and oblate spheroid weights, early medieval activities became evident but cannot be specified further. The topographical situation of the site, at a hilltop and close to the shore of the Schlei inlet, as well as the proximity to other prominent Viking Age sites near Kosel, made an investigation promising. Subsequently, geoarchaeological prospection surveys on the farmlands revealed a prominent geological structure and a concentration of presumably anthropogenic structures, which in combination with the metal detector finds and the topographical as well as archaeological context clearly suggest Viking Age occupation activities. Even if an exact interpretation of the site must remain open for the time being, the identification of a new site of the Early Middle Ages can provide new impulses for the archaeology of the Viking Age Schlei.